PENGARUH SUMBER DAYA MANUSIA DAN KETRAMPILAN TERHADAP MODAL SERTA IMPLIKASINYA TERHADAP KINERJA PENGRAJIN JUMPUTAN DI PALEMBANG (STUDI KASUS KELURAHAN TUAN KENTANG DAN 30 ILIR) - Yun Suprani; Muhammad Said (JURNAL KOMPETITIF, 2020)
This research was based on research conducted by the author on 30 respondents jumputan business in Palembang. This research was conducted within 6 months, where the research was conducted using the SPPS 17 program. From the results of SPSS 17 calculations, the PLS-SEM equation is obtained as follows: Capital = 0.469 * HR + 0.290 * Skills, Performance = 0.353 * HR + 0.316 * Skill + 0.261 * Capital. The direct effect of each variable is as follows: Human Resources has a significant effect on Capital. Likewise, the effect of significant Skills on Capital. While the influence of Human Resources is significant on Performance. And the influence of Skills is significant on Performance. Indirect Effects (Indirect Effects) Significant Human Resources on performance mediated by venture capital Crafters of jumping business in Palembang there are no Indirect Effects (Indirect Effedan cts) Skills on performance mediated by the business capital of the business of the business of the business of the Jumping business in Palembang Keywords :Human Resources, Skills, Capital, and Performance